Análisis de congestionamiento vehicular para la optimización de los semáforos desde el redondel el cambio hasta el distribuidor el bananero - Sánchez Arpi, Pedro Pablo (2017)
At present, road traffic control systems have become essential due to the great congestion produced at intersections, as these are responsible for regulating vehicular traffic and avoiding accidents that affect the lives of pedestrians and drivers. For proper use of traffic light systems, it is important that they are operating according to the volume of vehicular traffic, because these can also generate congestion if they are not properly regulated. These in the waiting times can produce prolonged queues of vehicles that alter the traffic, thus generating bottlenecks and in turn fatigue and stress in the conductors. The object of our study is located on the avenue June 25th, which is the main entrance to the City of Machala, in the section from the El Bananero ring road to the El Cambio ring road, with the traffic lights located in front of the three most important shopping centers of the city, the CC. Paseo Shopping, the CC. Oro Plaza and Boyacá Stores. An interview was made to Ing. Osvaldo Blacio, Machala Mobility Traffic Signaling and Signaling Supervisor about the traffic lights located throughout the section of the 25th of June avenue from the El Bananero roundabout to El Cambio roundabout and informed us that those Traffic lights were located for different purposes such as: traffic lights that are in front of the CC. Paseo Shopping were located and regulated specifically for pedestrian use; Those facing CC. Oro Plaza were specifically located for vehicles returning to the city center from the CC. Paseo Shopping, and the traffic light in front of Warehouses Boyacá was located specifically for two returns and not for pedestrian use. Regarding the traffic lights located at the intersection with the avenue coming from the new land terminal, we were informed that these are not in operation at the moment because the demand for vehicular traffic that will circulate through this route is not known. Each traffic light is regulated according to the purpose they had to be placed. Meanwhile, a count of vehicles at the traffic lights, the number of vehicles stopped in red color and the ones that circulated in green color were realized, and the times of regulation of each semaphore were realized during five days of the week. With this information we were able to perform the analysis through the Queue Theory and we obtained a reliable result, since there is still no congestion point due to the traffic lights. An analysis was made regarding the vehicular traffic generated by each semaphore both inbound and outbound to the city, since it seems that in peak hours the traffic flow increases. However, in spite of the positive results of the analysis, a modeling and simulation could be carried out through the software Synchro 8, through which the current intervals were optimized, in order to improve the fluidity and the service levels in the transit of this area.